Anomaly Detection in Text Data Sets Using Character-Level Representation - Mohaghegh, Mahsa; Abdurakhmanov, Amantay (Institute of Physics (IoP), 2021)
This paper proposes a character-level representation of unsupervised text data sets for anomaly detection problems. An empirical examination of the character-level text representation was conducted to demonstrate the ability to separate outlying and normal records using an ensemble of multiple classic numerical anomaly classifiers. Experimental results obtained on two different data sets confirmed the applicability of the developed unsupervised model to detect outlying instances in various real-world scenarios, providing the opportunity to quickly assess a large amount of textual data in terms of information consistency and conformity without knowledge of the data content itself.
Keywords: 0202 Atomic, Molecular, Nuclear, Particle and Plasma Physics; 0204 Condensed Matter Physics; 0299 Other Physical Sciences; 51 Physical sciences